The Influence of the Problem-Based Learning (PBL) Learning Model on Social Studies Interest and Learning Outcomes - Ni Nyoman Satriani; Lasmawan, I Wayan; Kertih, I Wayan (Indonesian Journal of Instruction, 2025)
Social Studies learning in elementary schools still encounters the problem of low student achievement, caused by teacher-centered approaches that emphasize rote memorization. This condition limits students' active participation in the learning process and reduces their interest and critical thinking skills. This study aims to analyze the effect of the Problem Based Learning (PBL) model on students’ learning interest and learning outcomes in Social Studies. This research employed a quasi-experimental method with a post-test only control group design. The subjects involved 50 fifth-grade students, divided into an experimental class and a control class, each consisting of 25 students, selected through cluster random sampling. Data were collected using objective tests, interest questionnaires, interview guidelines, and observation sheets. Data analysis was conducted using MANOVA. The results revealed that the average learning interest and outcomes of students in the experimental class were higher than those in the control class. The MANOVA test showed a Wilks' Lambda value of 0.458, F = 20.462, with a significance level of 0.000, indicating a significant simultaneous difference between the two groups. These findings suggest that implementing the PBL model is effective in enhancing students' interest and learning outcomes in Social Studies. The implication of this study recommends integrating problem-based learning models to create active, meaningful, and competence-oriented learning environments.